Prophylactic Cancer Vaccines Engineered to Elicit Specific Adaptive Immune Response - Crews, Davis W.; Dombroski, Jenna A.; King, Michael R. (Frontiers in Oncology, 2021)
Vaccines have been used to prevent and eradicate different diseases for over 200 years, and new vaccine technologies have the potential to prevent many common illnesses. Cancer, despite many advances in therapeutics, is still the second leading causes of death in the United States. Prophylactic, or preventative, cancer vaccines have the potential to reduce cancer prevalence by initiating a specific immune response that will target cancer before it can develop. Cancer vaccines can include many different components, such as peptides and carbohydrates, and be fabricated for delivery using a variety of means including through incorporation of stabilizing chemicals like polyethylene glycol (PEG) and pan-DR helper T-lymphocyte epitope (PADRE), fusion with antigen-presenting cells (APCs), microneedle patches, and liposomal encapsulation. There are currently five cancer vaccines used in the clinic, protecting against either human papillomavirus (HPV) or hepatitis B virus (HBV), and preventing several different types of cancer including cervical and oral cancer. Prophylactic cancer vaccines can promote three different types of adaptive responses: humoral (B cell, or antibody-mediated), cellular (T cell) or a combination of the two types. Each vaccine has its advantages and challenges at eliciting an adaptive immune response, but these prophylactic cancer vaccines in development have the potential to prevent or delay tumor development, and reduce the incidence of many common cancers.